1986
DOI: 10.1002/tox.2540010305
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects testing with quantitative microbial analysis: Chemical signatures correlated with in situ biofilm analysis by FT/IR

Abstract: Chemical measures for the biomass, community structure, nutritional status, and metabolic activities of the microbiota have shown a remarkable responsiveness to changes in the bulk fluid physical and chemical properties, the chemistry, biodegradability, and microtopology of the surfaces, as well as biological factors such as predation. Chemical analysis of the microbiota (bacteria, algae, fungi, protozoa, and micrometazoa with their extracellular products <0.5mm in diameter) does not require quantitative relea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…When methane was utilized as carbon source in mineral salts agar, pink colonies typical of type II methane oxidizers were isolated. These monocultures displayed high proportions of the unusual PLFA, 18: lw8c which to date has only been found in type II methane-oxidizing bacteria [14][15][16] and that has been found consistently when soils are exposed to air and methane [17]. The PLFA representative of propane-utilizing isolates were not detected in these methane-utilizing organisms ( Table 4).…”
Section: Plfa Patterns Of Monocultures Isolated With Propane or Methamentioning
confidence: 95%
See 2 more Smart Citations
“…When methane was utilized as carbon source in mineral salts agar, pink colonies typical of type II methane oxidizers were isolated. These monocultures displayed high proportions of the unusual PLFA, 18: lw8c which to date has only been found in type II methane-oxidizing bacteria [14][15][16] and that has been found consistently when soils are exposed to air and methane [17]. The PLFA representative of propane-utilizing isolates were not detected in these methane-utilizing organisms ( Table 4).…”
Section: Plfa Patterns Of Monocultures Isolated With Propane or Methamentioning
confidence: 95%
“…If specific biomarker component patterns can be related to specific subsets of the microbial community, then the patterns can be used to define the microbial community structure. PLFA are presently the most sensitive and useful chemical measures of community structure [17]. The validation of the use of biomarkers as 'signatures' for particular groups of organisms has been based on the induction of shifts in microbial community structure by altering the microenvironment with resulting changes that can often be predicted (such as the formation of fungus 'heaven' and 'hell' on biofilms suspended in a subtropical estuary by manipulation of nutrients and inhibitors) [18].…”
Section: Usefulness Of Biomarkers To Define Shifts In Microbial Commumentioning
confidence: 99%
See 1 more Smart Citation
“…There is still little information about the significance or time scale of variability caused by environmental factors on PLFA profiles in natural systems. White (37) suggested that the conditions of growth allowing survival in a highly competitive consortium of microorganisms would severely restrict this kind of variability. However, in surface soils there may be significant temperature variations, to which large parts of the microbial community respond in a similar way.…”
Section: Pc1mentioning
confidence: 99%
“…Specialists have turned to the disciplines of molecular biology and genetics, analytical microbiology, and others in order to develop and apply new methods to the experimental problems of microbial systems analysis. These experimental tools are now being applied and tested and are becoming available for use in the structuring and analysis of mixed microbial systems (8,9). Because of the difficulties noted above and additional uncertainties arising from the nonlinear mathematics needed to describe the dynamical behavior and the time-varient nature of operating microbial systems, the ability to propose an a priori dynamical model and to successfully test it in an experimental system which has some relevance to real environmental systems is limited (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%